A Novel Study to Predict Trends and Policies for Mobile Communication in Multienvironment Regions - Khattak, Shah Jahan; Khan, Bakhtair (Wireless Communications and Mobile Computing, 2018)
The research community has growing interest in the field of mobile phone applications due to its extensive usage in voice, data, video, and their combinations including data-voice and voice-video. The trends of mobile usage have paramount significance to formulate effective policies, to analyze human behavior, reliable prediction, and planning, for development and prosperity of any region in the globe. In this research, we explore the usage of mobile communication to analyze these trends; for this, we select Khyber Pakhtunkhwa (KPK), Pakistan, a multienvironment based on farmers, students, employees, and businessmen. A field survey is carried out by designing a detailed structural questionnaire for viable collection of data to have superior analysis of different multienvironment based classes. A statistical analysis is performed through hypotheses and chi-square test on a large dataset based on sufficient number of observations collected through primary survey for each class. The survey results are provided in number of graphical and numerical illustrations to predict the mobile usage trends, evidently and effectively, of the people of KPK. This study has practical and significant implications in understanding the behavioral intensions of the individuals making policies about mobile phone usage.